Actions of the antiseizure drug carbamazepine in the thalamic reticular nucleus: Potential mechanism of aggravating absence seizures - Sung-Soo Jang; Nicole Agranonik; John R. Huguenard (Proceedings of the National Academy of Sciences, 2025)
Carbamazepine (CBZ) is a widely used antiepileptic drug effective in managing partial and generalized tonic-clonic seizures. Despite its established therapeutic efficacy, CBZ has been reported to worsen seizures in another form of epilepsy, generalized absence seizures, in both clinical and experimental settings. In this study, we focused on thalamic reticular (RT) neurons, which regulate thalamocortical network activity in absence seizures, to investigate whether CBZ alters their excitability, thereby contributing to the exacerbation of seizures. Using ex vivo whole-cell patch-clamp electrophysiology, we found that CBZ selectively inhibits the tonic firing of RT neurons in a dose-dependent manner without affecting burst firing. At the RT-thalamocortical synapse, CBZ significantly increases the failure rate of GABAergic synaptic transmission, with greater effects on somatostatin–than parvalbumin-expressing RT neurons. In vivo EEG recordings and open-field behavior in Scn8a med± mouse model confirmed that CBZ treatment exacerbates absence seizures, increasing both seizure frequency and duration while reducing locomotor activity. In addition, CBZ further amplifies the preexisting reduction in tonic firing of RT neurons in Scn8a med± mice. These findings uncover a mechanism by which CBZ exacerbates absence seizures through selective inhibition of RT neuron excitability and disruption of GABAergic synaptic transmission. This work provides mechanistic insights into the paradoxical effects of CBZ and suggests potential avenues for optimizing epilepsy treatment strategies.